New Management of Solid Cystic Craniopharyngioma: Intracavitary Bleomycin Plus Neuroendoscopic Resection - Alvarez Peña, Carlos (1999)
The autors present in a preliminary way, the management and clinical course of a 9-year-old girl harboring a solid craniopharyngioma with a giant cystic component. She was treated with an overall intracavitary administration of 94,20 mg of bleomycin through a like-Ommaya reservoir plus tumor resection and third ventriculostomy, both neuroendoscopically. Clinical course was optimal and she was discharged with partial visual recovery without intracraneal hypertension. We hope maximal resolution after a few months.